Nomogram Based on Preoperative Fibrinogen and Systemic Immune-Inflammation Index Predicting Recurrence and Prognosis of Patients with Borrmann Type III Advanced Gastric Cancer - Wang H; Yin X; Ma K; Wang Y; Fang T; Zhang Y; Xue Y (Dove Medical Press, 2023)
Hao Wang,1,* Xin Yin,1,* Keru Ma,2,* Yufei Wang,1,* Tianyi Fang,1 Yao Zhang,1 Yingwei Xue1 1Department of Gastroenterological Surgery, Harbin Medical University Cancer Hospital, Harbin, People's Republic of China; 2Department of Thoracic Surgery, Esophagus and Mediastinum, Harbin Medical University Cancer Hospital, Harbin, People's Republic of China*These authors contributed equally to this workCorrespondence: Yingwei Xue, Department of Gastrointestinal Surgery, Harbin Medical University Cancer Hospital, Harbin Medical University, Harbin, 150081, People's Republic of China, Tel +86-13304646901, Email xueyingwei@hrbmu.edu.cnBackground and Objectives: The prognosis is known to differ significantly among advanced gastric cancer (AGC) with Borrmann type III. This study aimed to evaluate the prognosis of these patients more individually.Methods: We selected 542 AGC patients with Borrmann type III. We used the receiver operating characteristic curve to analyze the cutoff values of inflammation indexes, and used Kaplan-Meier and Log rank tests to analyze recurrence-free survival (RFS) and overall survival (OS). The independent risk factors for recurrence and prognosis were analyzed by Cox proportional hazards regression model. The nomogram models were constructed by R studio.Results: Patients with high preoperative fibrinogen (F) and systemic immune-inflammation index (SII) levels had worse RFS and OS and higher risk of postoperative locoregional recurrence, hematogenous metastasis and lymph node metastasis. F and SII can combine with different clinicopathological features (all P< 0.05) to construct nomograms to predict 5-year recurrence and prognosis, which both were superior to pTNM stage alone.Conclusion: The nomogram models based on F and SII can evaluate AGC with Borrmann type III postoperative recurrence and prognosis.Keywords: gastric cancer, Borrmann classification, fibrinogen, systemic immune-inflammation index, recurrence, nomogram